Optical Detection and Efficient Removal of Transition Metal Ions from Water using Poly(hydroxamic acid) Ligand - Lutfor, M. R.; Sarkar, Shaheen M.; M. M., Yusoff; Mohd Harun, Abdullah (Elsevier Ltd, 2017)
A copolymer, cellulose-graft-poly(methyl acrylate), was synthesized by a free-radical initiating process, and the ester functional groups converted into the hydroxamic acid ligand. The pH of the solution acts as a key factor in achieving optical color signals of metal-complexation. The reflectance spectra of the [M-ligand]n+ complex was found to be at the highest absorbance, ranging from 92 to 99% at pH 6, with absorbance noted to increase as metal ion concentrations were increased. A broad peak at 673 nm for Cu2+ was observed, indicating the presence of the charge transfer (π–π transition) complex. The developed ligand demonstrated superior adsorption capacity for copper (305.3 mg g−1), as well as strong adsorption capacity for other metals; the adsorption capacities for Fe3+, Mn2+, Co2+, Cr3+, Ni2+, and Zn2+ were 275.6, 258.5, 256.6, 254.3, 198.5, and 190.1 mg g−1, respectively. The experimental data of the adsorption kinetics of the metal ions fitted well with a pseudo-second-order rate equation. The obtained data demonstrated that the observed metal ion sorption was well fitted with the Langmuir isotherm model (R2 > 0.99), suggesting that the surface of the adsorbent is homogenous and monolayer. The reusability of the ligand was verified using the sorption/desorption process, demonstrating that the developed adsorbent can be reused for 12 cycles without significant loss of its original sensing and removal performance.